2016
DOI: 10.1364/ao.55.007462
|View full text |Cite
|
Sign up to set email alerts
|

Intensity fluctuations of asymmetrical optical beams in anisotropic turbulence

Abstract: Intensity fluctuations of asymmetrical optical beams are examined when such beams propagate through anisotropic turbulence. Anisotropic turbulence is modeled by non-Kolmogorov von Kármán spectrum. The variations of the scintillation index are observed against the changes in the asymmetry factor of the Gaussian beam, power law exponent of non-Kolmogorov spectrum, anisotropic factors in the transverse direction, and the link length. It is found that for all the conditions, asymmetry in the optical beam is a disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…where κ x , κ y , and κ z are spatial frequency components in the x, y, and z directions, respectively. According to the Markov approximation, we assume that the κ z component in the anisotropic oceanic turbulent medium can be ignored due to delta correlation and spatial frequency, and κ ξ ¼ ξκ p [22] . The power spectrum of the anisotropic turbulent ocean is [10]…”
Section: Snmentioning
confidence: 99%
See 1 more Smart Citation
“…where κ x , κ y , and κ z are spatial frequency components in the x, y, and z directions, respectively. According to the Markov approximation, we assume that the κ z component in the anisotropic oceanic turbulent medium can be ignored due to delta correlation and spatial frequency, and κ ξ ¼ ξκ p [22] . The power spectrum of the anisotropic turbulent ocean is [10]…”
Section: Snmentioning
confidence: 99%
“…These studies [17][18][19][20] cover the log-amplitude correlation function for spherical wave propagation through anisotropic non-Kolmogorov atmosphere, average polarization of the electromagnetic Gaussian Schell model beams propagating through anisotropic non-Kolmogorov turbulence, polarization of quantization Gaussian Schell beams through anisotropic non-Kolmogorov turbulence of the marine atmosphere, and effects of anisotropic turbulence on the average polarizability of Gaussian Schell model quantized beams through an ocean link. In our earlier studies, we have reported in anisotropic oceanic turbulence, the intensity fluctuations of spherical optical beams [21] , the intensity fluctuations [22] , and the bit error rate (BER) of asymmetrical Gaussian beams [23] . In these works, the observation is that anisotropy in the turbulent ocean causes reductions in the intensity fluctuations and BER.…”
mentioning
confidence: 99%
“…For optical wave propagation, the classic Kolmogorov model has been widely used in theoretical researches due to its simple mathematical form [3][4][5]. Over the years, the Kolmogorov model is extended and several non-Kolmogorov turbulence models have been also proposed [6][7][8][9][10][11][12][13]. Toselli et al [6] is one of them, and they analyze the angle of arrival fluctuations by using the generalized exponent factor α instead of the standard exponent value 11/3.…”
Section: Introductionmentioning
confidence: 99%
“…Toselli et al [6] is one of them, and they analyze the angle of arrival fluctuations by using the generalized exponent factor α instead of the standard exponent value 11/3. The anisotropic factor is also used to describe anisotropy of the atmosphere turbulence [7], and the generalized non-Kolmogorov von Karman spectrum of the anisotropic atmospheric turbulence is available [8][9][10]. In addition, there are also numerous studies on beam wanders, loss of spatial coherence, temporal frequency spread, and the angle of arrival fluctuation [14][15][16][17][18][19][20][21], which are all related to the random fluctuation of optical waves propagating through random media.…”
Section: Introductionmentioning
confidence: 99%
“…For the optical waves propagating in terrestrial or high altitude atmospheric turbulence, the classic Kolmogorov model has been widely used in theoretical research due to its simple mathematical form [2][3][4]. Over the years, the Kolmogorov model is extended and several non-Kolmogorov turbulence models have been also proposed [5][6][7][8][9]. Toselli is one of them and he analyzes the angle of arrival fluctuations by using the generalized exponent factor α instead of the standard exponent value 11/3 [5] and the anisotropic factor is also used to describe the anisotropy of the atmosphere turbulence [6].…”
Section: Introductionmentioning
confidence: 99%